Anatomical changes of the CNS in the course of schizophrenia and recurrent depression a review of current knowledge - Joanna Gmyz; Weronika Zubrzycka; Patrycja Grzech; Lena Kreczyńska (Journal of Education, Health and Sport)
Introduction and purpose of the study: Schizophrenia and recurrent depressive disorder are important mental disorders worthy of special interest in both the fields of psychiatry and neuroradiology. The studies presented in the following paper have made it possible to see a correlation between specific symptoms specific to the aforementioned disease entities and the location of pathological changes within the CNS.